Use of the ITS Marker to Detect Genetic Relationships among Ten Species of the Genus Brassica L. (Brassicaceae) in Central and Northern Iraq - Mohammad A. alblesh; Afrah S. Khaleel (Academia Open, 2026)
General Background: The family Brassicaceae includes many plant species distributed worldwide, with the genus Brassica representing an important taxonomic group. Specific Background: The internal transcribed spacer (ITS) region of nuclear ribosomal DNA is widely used as a molecular marker for identifying genetic variation and phylogenetic relationships among closely related plant species. Knowledge Gap: However, molecular studies examining genetic relationships of Brassica species in Iraq remain limited. Aims: This study analyzes genetic variation and phylogenetic relationships among ten Brassica species collected from central and northern Iraq using ITS-PCR sequencing. Results: ITS amplification produced DNA fragments of approximately 758 base pairs, and sequence comparison with the NCBI GenBank database confirmed the identification of the studied taxa. Phylogenetic analysis separated the species into two clusters: Group A containing eight species (B. deserti, B. nigra, B. deflexa, B. juncea, B. elongata, B. tournefortii, B. napus, and B. rapa) and Group B containing two species (B. aucheri and B. oleracea). Genetic distance ranged from 0.1639 to 7.8948, with the closest relationship between B. tournefortii and B. napus and the greatest divergence between B. aucheri and B. tournefortii. Novelty: This study provides molecular evidence of genetic relationships among Iraqi Brassica species based on ITS sequence analysis. Implications: The results contribute to understanding genetic diversity within the genus and support future taxonomic and genetic research on Brassica. Highlights:• Clear Its-Pcr Amplification Generated Dna Fragments of Approximately 758 Base Pairs for All Studied Taxa.• Phylogenetic Reconstruction Separated the Examined Species Into Two Major Genetic Clusters.• The Smallest Genetic Distance Occurred Between B. Tournefortii and B. Napus, While the Largest Divergence Involved B. Aucheri. Keywords: Brassica, ITS Marker, Phylogenetic Analysis, Genetic Distance, Brassicaceae